2019
DOI: 10.1128/mra.00601-19
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Hydrocarbon-Degrading Halotolerant Acinetobacter radioresistens DD78, Isolated from the Aconcagua River Mouth in Central Chile

Abstract: Acinetobacter radioresistens strain DD78 (= CCUG 69565) is a soil hydrocarbon-degrading and biosurfactant-producing bacterium isolated from chronically crude oil-polluted soil of the Aconcagua River mouth in Chile. The 3.25-Mb A. radioresistens DD78 genome (41.8% GC content) was completely sequenced, with 4 replicons, 2,970 coding sequences, and 77 tRNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…All alkane hydroxylases clustered into separate clusters on the phylogenetic tree and were genus related. The genetic organization of these genes was similar to that of the previously described Acinetobacter strains [ 11 , 36 , 37 , 38 ].…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…All alkane hydroxylases clustered into separate clusters on the phylogenetic tree and were genus related. The genetic organization of these genes was similar to that of the previously described Acinetobacter strains [ 11 , 36 , 37 , 38 ].…”
Section: Resultssupporting
confidence: 65%
“…Upstream of the ferredoxin gene, an AraC-type transcriptional regulator gene was identified that might be responsible for regulating the expression of P450 ( Figure 6 C). In the genome of strain DD78, the genes for two transposases belonging to the IS5 and Tn3 families are located near the P450 operon [ 36 ]. The same type of transposase-encoding genes were also found close to the P450 operon in the genome of the strain ICP1.…”
Section: Resultsmentioning
confidence: 99%
“…Acinetobacter sp. DD78 possess the ability to produce biosurfactants, which can help improve the bioavailability of the hydrocarbons for biodegradation [54]. The following two treatments were based on biostimulation with the addition of compost in two different ratios, 9:1 (v/v) and 3:2 (v/v), named BE1 and BE4, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Studies focused in hydrocarbon bioremediation have highlighted the potential of exploring microorganisms containing genes related to hydrocarbon-degrading enzymes ( 1 , 2 ). Specifically, bacteria belonging to genera Pseudomonas ( 3 ) and Acinetobacter ( 4 ) have shown potential to degrade alkanes and aromatic hydrocarbons ( 5 , 6 ). Here, we report the genomic sequencing of three strains retrieved from an abandoned old-century oil exploration well, located in the Cahuita National Park, Costa Rica, which is characterized by a continuous efflux of methane and the presence of a complex mixture of hydrocarbons ( 7 ).…”
Section: Announcementmentioning
confidence: 99%